HUBUNGAN POLA KONSUMSI PANGAN HARIAN DAN AKTIVITAS FISIK TERHADAP STATUS GIZI SISWA SMK KESEHATAN SURABAYA - Hidayati, Nurul; Nisak, Siti Khoirotun; Winiastri, Dinda (Ensiklopedia of Journal, 2025)
Background: The issues of overnutrition and undernutrition remain significant challenges among adolescents, often associated with imbalanced dietary patterns and physical inactivity. This study aimed to analyze the relationship between daily food consumption patterns and physical activity with the nutritional status of students at the Surabaya Health Vocational High School. Methods: This cross-sectional study involved 40 students selected as samples. Data on consumption patterns and physical activity were collected via questionnaires, while nutritional status was determined through anthropometric measurements (Body Mass Index for Age). Data were analyzed using statistical tests to examine the relationships between variables. Results: The results showed that 62.5% of students had a normal nutritional status, 27.5% were undernourished, and 10% were overweight. The majority of students (67.5%) had abnormal protein intake. Statistical analysis revealed a significant relationship between daily food consumption patterns and nutritional status (p=0.006), as well as between physical activity and nutritional status (p=0.008). Conclusion: Both daily food consumption patterns and physical activity are significantly associated with the nutritional status of students. Promotive efforts to enhance healthy living behaviors are essential. Keywords: Nutritional Status, Consumption Patterns, Physical Activity